Wavelet-based EEG processing for computer-aided seizure detection and epilepsy diagnosis. (March 2015) - Faust, Oliver; Acharya, U. Rajendra; Adeli, Hojjat; Adeli, Amir
Highlights: Wavelet techniques used for computer-aided seizure detection are presented. Epilepsy diagnosis with an emphasis on research reported during the past decade is discussed. A multi-paradigm approach advanced by Adeli and associates is described. Abstract: Electroencephalography (EEG) is an important tool for studying the human brain activity and epileptic processes in particular. EEG signals provide important information about epileptogenic networks that must be analyzed and understood before the initiation of therapeutic procedures. Very small variations in EEG signals depict a definite type of brain abnormality. The challenge is to design and develop signal processing algorithms which extract this subtle information and use it for diagnosis, monitoring and treatment of patients with epilepsy. This paper presents a review of wavelet techniques for computer-aided seizure detection and epilepsy diagnosis with an emphasis on research reported during the past decade. A multiparadigm approach based on the integration of wavelets, nonlinear dynamics and chaos theory, and neural networks advanced by Adeli and associates is the most effective method for automated EEG-based diagnosis of epilepsy.